Power, brokers, and agendas: New directions for the use of social network analysis in education policy - Hodge, Emily; Childs, Joshua; Au, Wayne (Education Policy Analysis Archives, 2020)
In this special issue, Researching 21st Century Education Policy Through Social Network Analysis, authors use social network analysis (SNA) to explore policy networks, broaden the current literature of sociological approaches to SNA, and/or incorporate new lenses for interpreting policy networks from political science or other academic disciplines. This editorial introduction first provides an overview of policy networks and their relevance in education. Then, the editors describe existing work applying the tools of SNA to education policy and highlight understudied areas before describing the articles included in this issue. These articles apply SNA to a variety of education policy issues, including large scale policies such as the Every Student Succeeds Act and the Common Core State Standards, charter schools, and the relationship between system and non-system actors. Articles highlight multiple applications of SNA, including how SNA can be used to advance theory, as well as describe and predict policy networks.